The metamorphoses of illegitimacy in São Jorge Island (Azores, Portugal) 1600–1910 - Matos, P. T. de. (History of the Family, 2026)
This article examines illegitimacy in the Azores from a long-term perspective (c. 1600–1910), using the island of São Jorge as a case study. It combines an island-wide approach with a bottom-up analysis centered on the parish of Ribeira Seca, drawing on parish registers, family reconstitution, nominal population lists, ecclesiastical documentation, and judicial records. While the chronological scope spans the early modern and modern periods, the analysis of individual life courses focuses primarily on the eighteenth and nineteenth centuries. The article argues that illegitimacy in São Jorge cannot be adequately understood as moral deviance or as a straightforward consequence of poverty. Instead, it constituted a structural – and often transitional – feature of local society, shaped by enduring constraints on access to marriage, a marked degree of social tolerance towards non-marital motherhood, and locally embedded forms of accommodation. Despite very high levels of non-marital fertility, child abandonment remained comparatively limited, pointing to informal mechanisms that integrated single mothers and their children into family and household structures. The analysis shows that a substantial proportion of children born outside marriage later acquired legitimate status through parental marriage or paternal acknowledgement. Reproduction prior to marriage often did not represent a break with matrimonial norms, but rather a sometimes prolonged and uncertain path toward the formation of a legitimate family. By situating São Jorge within both the Azorean and broader European contexts, the article identifies an exceptional insular trajectory and suggests that its high levels of illegitimacy are best explained by the interaction of demographic constraints and a distinctive local cultural configuration.